ANALISIS EKSTRAKURIKULER SENI TARI DALAM MENANAMKAN CINTA TANAH AIR SISWA KELAS V MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Syalwa Syalsabiluna; Dewi Utami; Irvan Iswandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Elementary school is a crucial stage in shaping children's character. At this age, they are in the golden age of moral and social development. Amid the strong current of globalization and rapid technological advancement, students are easily exposed to foreign cultures. Character education, especially the value of patriotism, serves as a shield to ensure that students maintain a sense of pride, care, and responsibility toward their nation. This study examines the implementation and analyzes the role of extracurricular dance activities in instilling patriotism among fifth-grade students at Madrasah Ibtidaiyah Ma’had Al-Zaytun. This research employed a qualitative descriptive method. Data collection techniques included observation, interviews, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing. The results show that the extracurricular dance activities at Madrasah Ibtidaiyah Ma’had Al-Zaytun are implemented through three consistent stages: preparation, implementation, and evaluation with reflection. These activities do not merely focus on movement skills but also provide students with an understanding of the background, cultural values, and meanings of each traditional dance taught. The dance materials are carefully selected based on students’ backgrounds, abilities, and interests, and are delivered gradually using a contextual approach in an enjoyable learning environment. This activity plays a strategic role in instilling the character of patriotism through three aspects: introducing the nation's cultural richness, fostering pride in traditional dance, and forming a commitment to preserve cultural heritage. This role is clearly reflected in students’ changes in attitude, showing pride, enthusiasm, and awareness of the importance of preserving Indonesian culture. Thus, the internalization of patriotism values can occur naturally and effectively. Keywords: extracurricular, dance, character, love of the homeland, elementary school students